A new record of rare dinoflagellate species Protoperidinium carum (Abé, 1981) Balech, 1994 for Vietnamese waters and Southeast Asia region - Luom, Phan Tan (Vietnam Journal of Marine Science and Technology, 2020)
Although there were a number of studies on the section Oceanica of the genus Protoperidinium, most of the published figures did not well revealed the clear features of the anterior intercalary plates. In this paper, Protoperidinium carum was re-described in details of cell morphology, plate patterns and thecal ornamentation, especially the second anterior intercalary plate (2a) is wide pentagonal instead of hexagonal type as in the previous descriptions. This species was illustrated with line drawing, light and scanning electron microscope photographs. P. carum was newly recorded in Southeast Asia and Vietnamese waters.